The effectiveness of the ‘Lumbung Ilmu’ digital library as a learning resource reviewed from a sociology of technology perspective - Anggi Yus Susilowati (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. Limited learning resources are a major obstacle to improving the quality of education in Indonesia. Digital libraries offer a potential solution to the problem of accessibility to learning resources. This study aims to analyse the effectiveness of digital libraries as a source of learning for students, from a sociological perspective. Research Methods. A quantitative descriptive method was used with a population of students majoring in Sociology of Religion at UIN Siber Syekh Nurjati Cirebon. The sample was determined through purposive sampling. Data were collected through questionnaires, observations, and document studies, then analysed using statistical description techniques. Results. The results of the study show that the “Lumbung Ilmu” Digital Library significantly increases student productivity through efficient and flexible access. This implementation has successfully shifted learning behaviour to be more independent and encouraged a culture of scientific literature exploration in line with developments in modern learning styles. Conclusion. The development of the “Lumbung Ilmu” Digital Library has proven effective in meeting the literature needs of Religious Sociology students and has become an adaptive medium that optimises the integration of technology in the higher education ecosystem to support social learning activities.